2020
DOI: 10.1101/2020.06.05.137174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differences in metabolic and liver pathobiology induced by two dietary mouse models of nonalcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a growing epidemic associated with key aspects of metabolic disease such as obesity and diabetes. The first stage of NAFLD is characterized by lipid accumulation in hepatocytes, but this can further progress into non-alcoholic steatohepatitis (NASH), fibrosis or cirrhosis, and hepatocellular carcinoma (HCC). A western diet, high in fats, sugars and cholesterol is linked to NAFLD development. Murine models are often used to experimentally study NAFLD, as they can dis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…The progression of HFCF-induced NASH in female mice is not extensively explored. Nonetheless, it was recently reported that long-term feeding (>30 weeks) with NASH- inducing diets promotes NASH with fibrosis in female mice, but at a lesser level than males [53, 54]. We also show that NASH is more accentuated in males than females with pre-established diet-induced obesity, with a significant staining of collagen fibers in male mice just after 16 weeks of HFCF diet.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The progression of HFCF-induced NASH in female mice is not extensively explored. Nonetheless, it was recently reported that long-term feeding (>30 weeks) with NASH- inducing diets promotes NASH with fibrosis in female mice, but at a lesser level than males [53, 54]. We also show that NASH is more accentuated in males than females with pre-established diet-induced obesity, with a significant staining of collagen fibers in male mice just after 16 weeks of HFCF diet.…”
Section: Discussionsupporting
confidence: 61%
“…Although the Amylin liver NASH (AMLN) diet or the Gubra AMLN (GAN) diet required more than 30 weeks to induced NASH in male mice [26, 44], these diets induce NASH after 16 weeks of feeding in leptin-deficient hyperphagic mouse model (ob/ob) [26, 56]. It should be noted that long term feeding of AMLN and GAN diets does not promote adiposity as 16 weeks of HFD-feeding [24, 53], despite the GAN diet increasing fat mass tissue [44]. This evidence suggests that inducing obesity and human-like NASH together in mice is a challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard rodent diet contains relatively little dietary fat, and mice fed this diet typically do not develop fatty liver disease. In (legend continued on next page) ll Article contrast, when rodents are fed a diet rich in fat (Western-type diet; WD), they accumulate significantly more TAGs in the liver, reminiscent of NAFLD (Zhang et al, 2020). To better understand the role of FXR in controlling elevated hepatic lipid levels, we fed wild-type and Fxr À/À mice WD for 8 weeks to promote hepatic lipid accumulation.…”
Section: In An Nafld Model Fxr Activation Dramatically Decreases Hepa...mentioning
confidence: 99%
“…Consumption of a high-calorie diet with high fat and high sugar (western diet) results in weight gain and is the initial event for the development of fatty liver ( 125 127 ). Particular types of lipids and carbohydrates play important roles in the progression of NASH.…”
Section: Pathogenesis Of Nafl/nashmentioning
confidence: 99%